2008
DOI: 10.2225/vol11/issue4-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of a putative crustacean hyperglycemic hormone of Litopenaeus vannamei in Pichia pastoris

Abstract: Crustacean hyperglycemic hormone (CHH) is the most abundant and best studied member of the CHH/MIH/GIH neuropeptide hormone family. CHH plays a major role in controlling glucose levels in the hemolymph, and it also has significance in regulating molting, reproduction, and osmoregulation. In contrast, molt-inhibiting hormone (MIH) is responsible for maintaining animals in an intermolt stage. In this study, Liv-MIH-1 cDNA, which encodes a mature neuropeptide from the eyestalk of white shrimp, Litopenaeus vanname… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Interestingly, we found that CHH-B1 has hyperglycemic activity even though the sequence of the native CHH-B1 suggests that it has a free C-terminus. Our present results confirmed the hyperglycemic activity that was previously observed using a CHH-B1 recombinant version having 26 additional amino acids at the C-terminal end, constructed previously by our group using unilaterally ablated shrimp [30].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, we found that CHH-B1 has hyperglycemic activity even though the sequence of the native CHH-B1 suggests that it has a free C-terminus. Our present results confirmed the hyperglycemic activity that was previously observed using a CHH-B1 recombinant version having 26 additional amino acids at the C-terminal end, constructed previously by our group using unilaterally ablated shrimp [30].…”
Section: Discussionsupporting
confidence: 92%
“…The expression of rCHH-B1 was induced according to the method described by Sánchez-Castrejón et al [30] with some modifications. A colony of P. pastoris X-33 containing pPicZ␣A-CHH-B1a inserted into its genome was grown in 3 mL of YPD medium (1% yeast extract, 2% peptone, 2% dextrose, 100 g/mL zeocin) for 18 h at 30 • C and 200 rpm.…”
Section: Expression Of Rchh-b1mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the use of the DNA recombinant technology has been useful in generating these crustacean peptides in sufficient quantities to enable furthermore studies of their physiological roles (Okumura 2004). Until now, the recombinant CHHs (rCHHs) have been obtained by bacterial (Gu, Yu & Chan 2000;Katayama, Ohira, Aida & Nagasawa 2002;Mettulio, Edomi, Ferrero, Lorenzon & Giulianini 2004a;Ohira, Tsutsui, Nagasawa & Wilder 2006;Mosco, Edomi, Guarnaccia, Lorenzon, Pongor, Ferrero & Giulianini 2008) or yeast expression systems (Ohira, Katayama, Aida & Nagasawa 2003;Udomkit, Treerattrakool & Panyim 2004;Sánchez-Castrejón, Ponce-Rivas, Aguilar & Díaz 2008) but the majority of the rCHH proteins expressed in Escherichia coli has been obtained as insoluble aggregates (Gu et al 2000;Katayama et al 2002;Ohira et al 2006;Mosco et al 2008). On the other hand, although the CHH protein has been expressed in a soluble form and biologically active in the yeast expression system, it has been shown that their yield is much less than that obtained in E. coli (Udomkit et al 2004).…”
Section: Introductionmentioning
confidence: 99%